The nature and effects of remittance scripts in rural Kosovo - Judith Möllers; Arjola Arapi-Gjini (Migration Studies, 2024)
Remittances play an essential role in the interlinkage of migration and development. While past research has focused mainly on the monetary flows and their determinants, this article offers a deeper understanding of remitting as a social practice. Our research contributes to the emerging literature on remittance transfers in several directions. Using a rich ethnographic dataset of an area described as the quintessential land of migration, Opoja in Kosovo, it offers intriguing insights into the reasons and patterns behind remitting or `remittance scripts'. Our work complements the existing literature with a unique empirical analysis of changing remittance scripts over time and a discussion of the implications of such changes in terms of well-being in a rural context. By applying Carling's concept of scripting remittances, the study makes an important contribution to testing this concept. Our findings exemplify how a conservative rural environment may slow down a shift away from traditional remittance scripts. The analysis revealed how remittances unfold not only positive effects, such as contributing to the village's monetary well-being, but also various adverse effects. We identify a cautious development towards a new and still fragile script system, in which recipients provide social visibility as the core requital to the remittances they receive. Although remittance scripts are doubtlessly region-specific, we believe that our study not only underlines the usefulness of the remittance script concept but is illustrative of phenomena that might be found in many places strongly affected by outmigration and remittance dependency.
Keywords: 300; remittance scripts; migration; well-being; Kosovo